Biography of an idea : memoirs of Public Relations Counsel - Bernays, Edward L., 1891-1995 (New York Simon and Schuster, 1965)
This article presents information regarding the book "Biography of an Idea: Memoirs of Public Relations Counsel Edward L. Bernays." People have become used to famous lawyers and doctors writing their memoirs, thus establishing themselves in the public mind as interesting people in vital professions. Up until now, the public has had no occasion to really know a public relations man. And such books that have been written by public relations leaders have related primarily to their work, with little suggestion of their personalities. Edward L. Bernays breaks this barrier. His long career with well known people, his involvement in important social and economic and political issues, gives him the basic material that makes this book much more than a description of public relations techniques. By revealing himself as a warm person, with strong opinions about the issues of his times, by setting down intimate observations about famous persons, he conveys to the public the nature of public relations. Moreover, he shows public relations at work for the benefit of social causes, the arts, health and welfare, in addition to serving business.
En rev. : Public Relations Quarterly. Winter66, Vol. 10 Issue 3/4, p96. 6p.
Keywords: Relaciones públicas; Libros electrónicos